Unusual Surgical Resection of Asymptomatic Schwannoma of the Cervical Vagus Nerve With Risk of Stroke: Case Report - Roberto Sérgio Martins; Adilson J. M. de Oliveira; Evander Lucas; Mario Gilberto Siqueira (Case Reports in Surgery)
Schwannomas are the most common tumors of the peripheral nerves, originating from their support cells, the Schwann cells. The location of the tumor in the vagus nerve is rare. Vagus schwannomas usually present as a solitary, slow-growing, asymptomatic mass that rarely causes neurological alterations. The differential diagnosis of vagus nerve schwannomas includes other tumors of the parapharyngeal space or neoplasms of the jugular foramen. We report the case of a patient with an asymptomatic schwannoma of the vagus nerve involving important neck structures, with radiological compression of the carotid artery with a high risk of stroke; because of this, we underwent surgery using a transcervical approach with intracapsular excision of the tumor. The patient has a good outcome. In asymptomatic patients’ surgical indication is not an easy decision; in this case, the main reason for surgical indication was the risk of stroke with potential neurological sequels.